Penerapan dan Evaluasi Pendekatan Berbasis Teks dalam Pembelajaran BIPA di Hanoi, Vietnam - Rosendi Galih Susani (Jurnal Bahasa Indonesia bagi Penutur Asing, 2020)
BIPA students who learn texts in authentic social contexts will be more effective. Teachers may try to implement text-based approach. This research aims to describe implementations and evaluations of text-based approach of BIPA learning in Ha Noi, Vietnam. This qualitative research used descriptive method in which the subject was BIPA third-level students in Indonesia Center-Umah Indo and Ministry of Defense in Ha Noi, Vietnam. Observations were made for data collection. Journals and documentation books were used as data analysis references. The result shows that in the text-based approach implementation of BIPA learning, (1) learning goals analysis is required by implementing stages of building learners’ background, knowledge, modeling and arranging text collectively and individually (2) studies in finding advantages and challenges can be produced. The result can be used to implement BIPA learning based on text-based approach by observing learning goals and learners’ characteristic. Keywords: implementation, evaluation, and text-based approach